2023
DOI: 10.1101/2023.02.04.527050
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential CpG methylation atNnatin the early establishment of beta cell heterogeneity

Abstract: Beta cells within the pancreatic islet represent a heterogenous population wherein individual sub-groups of cells make distinct contributions to the overall control of insulin secretion. The molecular mechanisms through which beta cell hierarchy is established remain poorly understood. The neuronatin (Nnat) gene is imprinted in mice and humans and is required for normal insulin synthesis and secretion. Here, we demonstrate that Nnat is differentially expressed in a discrete beta cell population in a developmen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 133 publications
(389 reference statements)
0
3
0
Order By: Relevance
“…NNAT is an imprinted proteolipid-encoding gene expressed specifically from the paternal allele that is highly expressed within differentiating endocrine cells and immature aggregating islet cells in mice (29, 30). Of note, a recent study showed that the mouse Nnat gene is differentially expressed across development in a discrete population of beta cells, and that this transcriptional plasticity is directly regulated by DNA methylation (31). The top hypomethylated dDMR (chr19: 16830287-16830859, 9 sites, P = < 1.14 x 10 -304 , Figure 2E ) spans the transcription start site (TSS) of the gene encoding WD repeat domain-containing protein 1 ( NWD1 ), which plays an important role in the developmental regulation of gene expression (32).…”
Section: Resultsmentioning
confidence: 99%
“…NNAT is an imprinted proteolipid-encoding gene expressed specifically from the paternal allele that is highly expressed within differentiating endocrine cells and immature aggregating islet cells in mice (29, 30). Of note, a recent study showed that the mouse Nnat gene is differentially expressed across development in a discrete population of beta cells, and that this transcriptional plasticity is directly regulated by DNA methylation (31). The top hypomethylated dDMR (chr19: 16830287-16830859, 9 sites, P = < 1.14 x 10 -304 , Figure 2E ) spans the transcription start site (TSS) of the gene encoding WD repeat domain-containing protein 1 ( NWD1 ), which plays an important role in the developmental regulation of gene expression (32).…”
Section: Resultsmentioning
confidence: 99%
“…Supernatants were subsequently acidified with 0.5% trifluoroacetic acid (TFA), followed by desalting using reversed-phase spin tips (Glygen Corp) and dried using vacuum centrifugation. Dried peptides were resuspended in 0.1% TFA and Liquid Chromatography Tandem Mass Spectrometry (LC-MS/MS) performed as previously described 65 using an Ultimate 3000 nano-HPLC coupled to a Q-Exactive mass spectrometer (Thermo Scientific) via an EASY-Spray source. Peptides were loaded onto a trap column (Acclaim PepMap 100 C18, 100 μm × 2 cm) at 8 μl/min in 2% acetonitrile, 0.1% TFA.…”
Section: Glp-1r Interactomementioning
confidence: 99%
“…NNAT is an imprinted proteolipid-encoding gene expressed specifically from the paternal allele that is highly expressed within differentiating endocrine cells and immature aggregating islet cells in mice [30,31]. Of note, a recent study showed that the mouse Nnat gene is differentially expressed across development in a discrete population of beta cells, and that this transcriptional plasticity is directly regulated by DNA methylation [32]. The top hypomethylated dDMR (chr19: 16,830,287-16830859, 9 sites, P = < 1.14 × 10 -304 , Fig.…”
Section: Development Of the Human Fetal Pancreas Is Associated With D...mentioning
confidence: 99%